An Exploration of Shifting Adolescent Use, Access and Risk Perception of Marijuana in the Caribbean Island of Barbados in 2006 and 2013. Issue 3 (4th May 2019) - Griffith, Alana D. D.; Cohall, Damian H.
Abstract: In the face of more liberal attitudes globally towards marijuana, its use by adolescents is considered harmful. Some Caribbean countries, including the island of Barbados, are deliberating changes to their drug policies on marijuana from complete prohibition towards more liberal approaches. There is a need for the analysis of existing use, access and risk perception of marijuana among Barbados' adolescent population given their vulnerability. This article employs data from two nationally representative secondary school surveys conducted in 2006 ( n  = 2239) and 2013 ( n  = 1339). A two-proportion z test was performed on the data to determine whether changes were significant at the 95% confidence level. While there has been an increase in prevalence and incidence rates, these were not significantly different in the two surveys. Significant changes were observed with the location of marijuana consumption and sources from which it was accessed. Finally, there was a significant decline in the perception that using marijuana regularly was harmful. Only the decline in frequent use being perceived as harmful was statistically significant. The results point to possible gaps in drug education and a greater need for the protection of the young.